The estimation of variability of morphological characteristic of generative sprout of Medicago daghestanica Rupr. еx Boiss. by the high-altitude factor in conditions intramountainous Dagestan - A. D. Кhabibov; D. M. Anatov; S. M. Zubairova; M. A. Magomedov (Юг России: экология, развитие, 2015)
The role of the high-altitude factor on interpopulation variability of morphological characteristic of generative sprout of Medicago daghestanica Rupr. еx Boiss. in the conditions of intramountainous Dagestan. The greatest indices of the majority of morphological characteristic are observed in population collected which was at a height 1400 m. above sea level. The linear characteristics which are bound with length of generative sprout and its components have considerable variations in development phases. The discrete signs have narrow variability in population. The high-altitude factor influences the majority of investigated signs in different degree with the exception of sign the length of racemiton.